Energetic costs and metabolic power variables from global positioning system (GPS) units for load monitoring in elite Australian football - Hull, A. R. (Journal of Australian Strength and Conditioning, 2018)
The purpose of this review of the literature was to critically analyse and evaluate the research regarding the use, reliability and validity of energetic costs and metabolic power variables from GPS units for load monitoring in elite AF. Movement demands of elite AF have been quantified using GPS devices and traditional time-based motion analyses. Recently, interest has grown in using these devices to quantify the energetic costs and metabolic power demands of these athletes. A scholarly search was performed which identified three relevant studies. Literature has reported that the average energy cost of elite AF match-play is 75.58 kj kg-1, while the average metabolic power for a match is 11.85 W kg-1. Energy cost decreases from the first to fourth quarters. Metabolic power is decreased in the second to fourth quarters compared to the first and is lowest in the fourth. Tall forwards (TF) accelerate less than midfielders (MID) and mobile backs (MB), while TF and RKS (rucks) also decelerate less than MF. GPS units overestimate energy expenditure during steady state walking by up to 40.7 kJ, and underestimate during intermittent exercise by up to 111.4 kJ. GPS derived metabolic power is 23% lower than indirect calorimetry metabolic power during soccer specific circuits. The units demonstrate poor intra-unit reliability with the number of accelerations and decelerations differing by up to 31 and 42% respectively. Inter-unit reliability has been shown to vary by 28-41% for accelerations, and 18-53% for decelerations. As accelerations and decelerations form the basis of energetic costs and metabolic power calculations, GPS units should not be used for load monitoring in elite AF.